2007
DOI: 10.1007/s10517-007-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome variability of human multipotent mesenchymal stromal cells

Abstract: We elaborated a method of preparing cytogenetic preparations of cultured multipotent mesenchymal stromal cells from the adipose tissue. It was found that karyotypic changes (monosomy, translocations) appear in some samples during culturing. Clones with changed karyotype were detected in 11-14-passage cultures from 2 of 7 individuals. The percent of aberrant cells in cultures from different individuals varied from 1.5 to 5.95 per 100 cells, which attested to karyotype instability. These data substantiate the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…Chromosomal aberration was found in late passages also by others (12,25). Therefore, our results support that ASC addressed to clinical use should be expanded only for few passages as well.…”
Section: Discussionsupporting
confidence: 84%
“…Chromosomal aberration was found in late passages also by others (12,25). Therefore, our results support that ASC addressed to clinical use should be expanded only for few passages as well.…”
Section: Discussionsupporting
confidence: 84%
“…All types of chromosome and genome mutations are detected in adult human SC cultures [1]. As the conditions of culturing and reinoculation of cell cultures are usually similar, the appearance of abnormal clones can be explained by their selective advantage in multiplication.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term culturing can lead to the appearance of cells with an abnormal karyotype, in addition to the selection of cells with a high proliferation rate. Therefore, cytogenetic stability and control are necessary for stem cells before transplantation to a donor organism (Bochkov et al 2007). We have shown that OC-RSCs not only maintain a high proliferative rate and purity after at least 8 passages, but also retain a normal diploid karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome preparations were made from the OC-RSCs at passage 8 and stained by conventional Giemsa staining as described by Bochkov et al (2007). In brief, colchicine (Sigma-Aldrich) at a final concentration of 0.01 µg/ml was added to flasks 1.5 h before fixation.…”
Section: Cytogenetic Analysismentioning
confidence: 99%